Role of Waqf in Social Welfare Financing in Nigeria - Adeola, Idowu Khadijah; Azeez, Oyedokun Olaitan; Oladehinde, Sikiru Taoheed (AIBPM Publisher, 2024)
This paper examined the role of waqf (endowment) on social welfare financing in Nigeria. Waqf, an endowment (donation), is one social welfare tool in Islam guided by Islamic law. Sustainable wellbeing is one of the goals of Waqf. This is one of the means through which Islam finances charitable organizations. The expository method is used in this work. In order to properly utilize permanent societal contributions, the institution of waqf can fill the void as a social finance institution by offering intermediation services. The waqf's flexible regulations allow it to offer a broad range of social services and to assist recipients directly or through financial institutions. The paper explained the concept of waqf and made a case for the practical applications of waqf; it recommended more public awareness of the institution and a more efficient means of leveraging the potential of altruistic giving for improved economic outcomes in the targeted social segments of society.